2018
DOI: 10.4097/kjae.2018.71.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of levobupivacaine and bupivacaine for bilateral maxillary nerve block during pediatric primary cleft palate surgery: a randomized double-blind controlled study

Abstract: BackgroundCleft lip and palate are common major congenital anomalies. Cleft palate (CP) repair causes pain and needs large doses of intravenous opioids. The risk of postoperative airway obstruction or respiratory depression is high, requiring continuous and vigilant monitoring. The primary outcome was to evaluate the efficacy of using different local anesthetics during bilateral maxillary nerve block (MNB) with general anesthesia on quality of recovery after primary CP repair. We hypothesized that levobupivaca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 23 publications
(27 reference statements)
0
35
0
Order By: Relevance
“…They concluded that the combination of dexmedetomidine and bupivacaine increased the analgesic duration after CP repair by 50% with no clinically relevant adverse effects. Mostafa et al [29] reported that the bilateral SMB is effective and safe for pain relief in children scheduled for primary CP repair surgeries with no severe side effects. They found that levobupivacaine is as effective as bupivacaine for SMB.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the combination of dexmedetomidine and bupivacaine increased the analgesic duration after CP repair by 50% with no clinically relevant adverse effects. Mostafa et al [29] reported that the bilateral SMB is effective and safe for pain relief in children scheduled for primary CP repair surgeries with no severe side effects. They found that levobupivacaine is as effective as bupivacaine for SMB.…”
Section: Discussionmentioning
confidence: 99%
“…Six of the 9 articles were prospective randomized clinical trials that reported multimodal management of postoperative pain in cleft lip and palate patients, and used opioids to manage postoperative pain. 7 , 8 , 11 13 , 15 These clinical trials reported a high statistical power in their studies (>80%) and included a total number of 321 patients. These studies evaluated the effect of multimodal analgesia by reducing the use of opioids that have been demonstrated to be efficacious in pain management.…”
Section: Resultsmentioning
confidence: 99%
“…Infraorbital, external nasal, and suprazygomatic nerve blocks have been used for pain management in these patients, and have resulted in good efficacy and low rates of adverse events. 7 , 8 , 11 …”
Section: Discussionmentioning
confidence: 99%
“…The maxillary nerve provides sensory innervation to the anterior and posterior palate, upper dental arch, maxillary sinus, and posterior nasal cavity. 9 The suprazygomatic approach to blocking the maxillary nerve has been shown to be effective at decreasing pain associated with trigeminal neuralgia and palatal surgery. 10,11 A double-blind randomized controlled trial showed a significant decrease in opioid consumption in cleft palate repair patients who received bilateral suprazygomatic maxillary nerve blocks.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 A double-blind randomized controlled trial showed a significant decrease in opioid consumption in cleft palate repair patients who received bilateral suprazygomatic maxillary nerve blocks. 9 By extension, orthognathic surgery in the form of Le Fort I maxillary advancement and/or distraction, involves the neurosensory distribution of the maxillary nerve. To our knowledge, this is the first study analyzing the effect of suprazygomatic maxillary nerve blocks on perioperative narcotic use in the setting of Le Fort I osteotomies.…”
Section: Introductionmentioning
confidence: 99%